Proses Individuasi Diri Tokoh Otosaka Yuu Dalam Anime “Charlotte”: Psikoanalisis Carl Gustav Jung - Maharani, Anastasia Widya Putri; Oemiati, Sri (Vocational College of Diponegoro University, 2025)
This study aims to analyze the individuation process of the main character in the anime Charlotte, Otosaka Yuu, using Carl Gustav Jung’s analytical psychology theory, specifically focusing on the integration of the four main archetypes: persona, shadow, anima, and self. Using a descriptive qualitative method, data were collected through careful observation of the anime, including transcripts of dialogue and relevant screenshots. The analysis reveals that Yuu experiences a complete process of individuation. Yuu gradually discards his persona and begins to live more authentically. Yuu’s shadow is acknowledged and accepted without being allowed to dominate his behavior. Yuu’s anima develops through his emotional connection with Nao, which helps him access his empathy and vulnerability. Ultimately, Yuu reaches the self, a state of psychological wholeness, marked by his willingness to sacrifice himself for others based on inner conviction rather than external validation. This transformation demonstrates that Yuu achieves an integrated and mature personality through his internal journey and interpersonal relationships. This analysis demonstrates how anime can depict complex psychological growth, offering valuable insights into character development and the symbolic representation of the human psyche in popular media. The study contributes to anime studies and highlights the applicability of Jungian theory to modern visual storytelling.